Determinants of Postpartum Hemorrhage Incidence in the Maospati Magetan Health Center Working Area in 2023, Indonesia - Dannisa Putri Dharma (Knowledge Dynamics, 2024)
Background: Postpartum hemorrhage (PPH) is a loss of blood of more than 500 ml that occurs after the birth of a child either before, during, or after the delivery of the placenta. In developing countries including Indonesia, PPH is the leading cause of maternal death, because of its rapid and unexpected occurrence. This study aims to determine the determinants of hemorrhagic postpartum incidence in Maospati Health Center in 2023. Methods: This type of research is using observational analytic with case control design. The sample in this study was a case sample with a total population of 9 birth mothers who experienced postpartum hemorrhage while the control sample with simple random sampling was randomly selected as many as 36 birth mothers who did not experience postpartum hemorrhage. Data collection techniques and instruments used secondary data from labor medical records in 2023. Data analysis used descriptive statistical methods with relative frequency distribution and proportion or percentage, analytical statistical methods with Chi-Square test, Logistic Regression Analysis and ODD Ratio. Results: Of the 10 determinants studied including that passed the candidate selection and Logistic Regression Analysis test were occupation p-value 0.253, parity p-value 0.137, anemia p-value 0.446, uterine subinvolution p-value 0.000. Conclusion: It can be concluded that occupation, parity, anemia have no influence on the incidence of postpartum hemorrhage while uterine subinvolution has a significant influence on the incidence of, which is 5 times more at risk of experiencing postpartum hemorrhage than mothers with no uterine subinvolution. Subinvolution uteri needs to be prioritized and should not be ignored in providing early treatment of postpartum hemorrhage with prevention efforts including fulfilling nutritional adequacy, conducting Early Breastfeeding Initiation, encouraging early and gradual mobilization, teaching uterine massage, teaching good attachment during breastfeeding, and postpartum exercises.